2013
DOI: 10.3389/fpsyg.2012.00616
|View full text |Cite
|
Sign up to set email alerts
|

Living Emotions, Avoiding Emotions: Behavioral Investigation of the Regulation of Socially Driven Emotions

Abstract: Emotion regulation is important for psychological well-being. Although it is known that alternative regulation strategies may have different emotional consequences, the effectiveness of such strategies for socially driven emotions remains unclear. In this study we investigated the efficacy of different forms of reappraisal on responses to the selfish and altruistic behavior of others in the Dictator Game. In Experiment 1, subjects mentalized the intentions of the other player in one condition, and took distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 54 publications
5
34
0
Order By: Relevance
“…Parallels can be made with the concepts of defense mechanisms in psychodynamic terms, and with dysfunctional regulatory strategies (Gross, 2011; Grecucci et al, 2013; Grecucci and Job, 2015). It includes three categories.…”
Section: Schema Therapy Model Of Emotion Dysregulation and Emotion Rementioning
confidence: 99%
See 1 more Smart Citation
“…Parallels can be made with the concepts of defense mechanisms in psychodynamic terms, and with dysfunctional regulatory strategies (Gross, 2011; Grecucci et al, 2013; Grecucci and Job, 2015). It includes three categories.…”
Section: Schema Therapy Model Of Emotion Dysregulation and Emotion Rementioning
confidence: 99%
“…In terms of emotion regulation science, these coping strategies belong to the class of “distancing” strategies, and produce an excessive down-regulation of (positive and negative) emotions (Grecucci et al, 2013, 2015a). …”
Section: Schema Therapy Model Of Emotion Dysregulation and Emotion Rementioning
confidence: 99%
“…These studies (Grecucci et al, 2013a,b) showed that an IER strategy of reappraising the intentions of the other player as less negative , or mentalizing-reappraisal (a particular kind of “reappraisal”), is effective in changing both interpersonal decisions (i.e., rejection rates of unfair offers in the context of a socio-economic game) (Grecucci et al, 2013a), as well-subjective responses to emotion themselves (Grecucci et al, 2013b). The task used in one of these experiments (Grecucci et al, 2013a) was the classic Ultimatum Game, where participants played the role of responder (Guth et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…ER can refer not only to people's capacity to manage their own emotions, but importantly can also extend to regulating emotions that result from the interaction with others (Grecucci, 2012; Grecucci et al, 2013b). Previous studies have examined the processes that individuals use to influence which emotions they generate, when they do so, and how these emotions are experienced or expressed (Gross, 1998), and therefore we know that different attentive, behavioral, emotional, or interpretative strategies can be used also at an interpersonal level (Fonagy, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation